How do you use the substitution method to solve 3x-15y=-12 and 3x+24y=-12?

1 Answer
Jun 26, 2015

Answer:

Derive an expression for #3x# from the first equation, then substitute that in the second equation and solve to find #y = 0# and #x = -4#

Explanation:

First add #15y# to both sides of the first equation to get:

[1] #3x=15y-12#

Then substitute #15y-12# for #3x# in the second equation to get:

#(15y-12)+24y=-12#

Add #12# to both sides and combine the remaining terms to get:

#39y = 0#

Divide both sides by #39# to get #y = 0#

Then substitute #y=0# in [1] to get:

#3x = -12#

Divide both sides by #3# to get #x = -4#